PENGARUH MODEL PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) TERHADAP KEMAMPUAN PEMBUKTIAN MATEMATIS DAN SELF-EFFICACY SISWA - Ummu Azizah; Anwar Mutaqin; Isna Rafianti (Universitas Sultan Ageng Tirtayasa, 2020)
This research aimed to find out whether Means Ends Analysis (MEA) model can affect the students’ mathematical proofs ability and self-efficacy positively. The research used quasi experimental through non equivalent control group design. The result of this research conclude that: (1) Means Ends Analysis learning model gave positive effect towards mathematical proofs ability, and (2) Means Ends Analysis model gave positive effect to the students’ self-efficacy.